ENHANCING LISTENING SKILLS BY USING PRAGMATIC APPROACH - Aritonang, Nia; TOGATOROP, RESTINA; MEY ARSEL; PURBA, SINTAULI; Tarigan, Sri Ninta (English Language Teaching Prima Journal (ELT), 2022)
This research is not only aimed to fulfill the final task but also to provide participation in the development of English language education in Indonesia. The method we use in this research is descriptive qualitative with data collected through face-to-face observations. The results showed that questionnaire media were very effective in enhancing students listening. The authors found that developing a student's thinking through enhancing listening skills using a pragmatic approach was very effective in increasing students' knowledge. Through this learning, several students who have been the target of this research, students feel that this learning is very simple and easy to understand, the way of learning is also interesting and simple. enhancing listening skills using pragmatic approach is very helpful to add and develop students' mindset